조생 단간 내도열병 뽀얀 중간찰 벼 ‘설백’ - 신영섭(Shin Young-Seop); 원용재(Yong-Jae Won); 안억근(Eok-Keun Ahn); 김연규(Yeon-Gyu Kim); 김명기(Myeong-Ki Kim); 황흥구(Hung-Goo Hwang); 윤영환(Young-Hwan Yoon); 이정희(Jeong-Heui Lee); 최임수(Im-Soo Choi); 윤광섭(Kwang-Sup Yoon); 오세관(Sea-Kwan Oh); 강경호(Kyeong-Ho Kang); et al. (Korean journal of breeding, 2012)
‘설백’은 조숙 내병 고품질 중간찰 계통을 육성할 목적으로 2000년 하계에 중간찰 품종인 수원460호에 조숙 내병 고품질 품종인 그루벼를 인공교배하여 2010년 육성된 조생 내도복 뽀얀 중간찰이다. ‘설백’은 보통기 보비재배에서 출수기는 평균 7월 29일로 ‘오대벼’보다 3일 빠른 조생종이다. ‘설백’의 간장은 60 cm이며, 주당수수는 13개, 수당립수는 81개이고, 천립중은 20.7 g으로 오대벼보다 가볍다. ‘설백’의 아밀로스함량은 10.0%로 중간찰이고 쌀 외관은 투명도가 5로 불투명해 보인다. ‘설백’은 위조에 강하고 불시출수가 잘 되지 않으며 성숙기에 하엽 노화가 느린 편이다. ‘설백’은 수발아에 강한 편이고, 내냉성은 ‘오대벼’와 비슷한 수준이다. 잎도열병에는 강한 저항성이고 흰잎마름병, 바이러스병 및 해충에는 약하다. 지역적응시험 보통기 보비재배에서 평균 쌀 수량이 4.96 MT/ha로 ‘오대벼’ 대비 92%의 수량성을 보였다. 재배적지는 중부평야지, 북부평야지, 중산간지, 남부고랭지 및 동북부해안지이다. The ‘Seolbaek’ is an early-maturing low amylose variety developed from a cross between ‘Suweon460’ and ‘Geuroobyeo’ by the rice breeding team of National Institute of Crop Science, Rural Development Administration (RDA) in 2000. The ‘Seolbaek’ has about 100 days duration from seeding to heading in middle plain, mid-northern inland plain, southern alpine and north-eastern coastal areas. It has about 60 cm in culm length with semi-erect plant type and good canopy architecture. This variety has 13 tillers per hill and 81 spikelets per panicle. Its 1,000 grain-weight of brown rice is 20.7 g whereas less than that of ‘Odaebyeo’ (26.3 g). The milled kernels look like dull because amylose content of this variety is about 10.0%. This variety shows strong resistance to cold treatment, lodging, and wilting. The ‘Seolbaek’ shows resistant to blast disease but susceptible to bacterial blight, stripe virus and insect pests. The milled rice yield performance of this variety is about 4.96 MT/ha by ordinary culture in local adaptability test for three years. This variety may be highly adaptable to the middle plain area, mid-northern inland plain area, southern alpine area and north-eastern coastal areas of Korea.